Feasibility test of agricultural residues through characterization for utilization in plasma gasification - GITANJALI, J; PUGALENDHI, S; KAMARAJ, S; KARTHIKEYAN, S; KUMAR, V J F (The Indian Journal of Agricultural Sciences, 2015)
Agricultural residues were characterized to determine their feasibility as feedstock for plasma gasification. Husk, stalk, straw and shell were selected for the study and proximate analysis, elemental composition analysis, thermal value analysis were carried out using standard procedures. Producer gas generated from these bio-residues is well suited for plasma gasification process where the working temperature is between 1200-2000ºC. These substances have moisture content in the range of 5-12%, and volatile matter content of 58-70%, offering good burning characteristics and conversion to electricity. The fixed carbon content of 13 to 20% contributes significantly to its calorific value. The average calorific value of selected agricultural residues (18.27 MJ/kg) was higher than the calorific value of feedstock (12 to 16 MJ/kg) used in plasma gasification, thus reinforcing their suitability further. It was found that selected agricultural residues could be adopted and promising fuel for plasma generation and deserve further development as a sustainable and renewable alternative.